Role of A(2B) Adenosine Receptors in Regulation of Paracrine Functions of Stem Cell Antigen 1-Positive Cardiac Stromal Cells - Ryzhov, Sergey (The American Society for Pharmacology and Experimental Therapeutics, 2012)
The existence of multipotent cardiac stromal cells expressing stem cell antigen (Sca)-1 has been reported, and their proangiogenic properties have been demonstrated in myocardial infarction models. In this study, we tested the hypothesis that stimulation of adenosine receptors on cardiac Sca-1(+) cells up-regulates their secretion of proangiogenic factors. We found that Sca-1 is expressed in subsets of mouse cardiac stromal CD31(−) and endothelial CD31(+) cells. The population of Sca-1(+)CD31(+) endothelial cells was significantly reduced, whereas the population of Sca-1(+)CD31(−) stromal cells was increased 1 week after myocardial infarction, indicating their relative functional importance in this pathophysiological process. An increase in adenosine levels in adenosine deaminase-deficient mice in vivo significantly augmented vascular endothelial growth factor (VEGF) production in cardiac Sca-1(+)CD31(−) stromal cells but not in Sca-1(+)CD31(+) endothelial cells. We found that mouse cardiac Sca-1(+)CD31(−) stromal cells predominantly express mRNA encoding A(2B) adenosine receptors. Stimulation of adenosine receptors significantly increased interleukin (IL)-6, CXCL1 (a mouse ortholog of human IL-8), and VEGF release from these cells. Using conditionally immortalized Sca-1(+)CD31(−) stromal cells obtained from wild-type and A(2B) receptor knockout mouse hearts, we demonstrated that A(2B) receptors are essential for adenosine-dependent up-regulation of their paracrine functions. We found that the human heart also harbors a population of stromal cells similar to the mouse cardiac Sca-1(+)CD31(−) stromal cells that increase release of IL-6, IL-8, and VEGF in response to A(2B) receptor stimulation. Thus, our study identified A(2B) adenosine receptors on cardiac stromal cells as potential targets for up-regulation of proangiogenic factors in the ischemic heart.